Nutritional Care Process for a Severe Communicating Hydrocephalus, Cerebral Edema, Microcephaly, Aspiration Pneumonia, and a History of Periodic Apnea - Helmi Susanti Simamora; Marselina Azalia Mahar; Aswita Amir; Hijrah Asikin (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
The Nutrition Care Process (NCP) provides a structured approach to identifying and addressing nutritional issues in such complex cases. This descriptive case study aims to evaluate the effectiveness of the NCP in improving nutritional intake and clinical outcomes, specifically the ability to cry loudly and engage in active movement. This study was conducted in the ICU of Dr. DORIS SYLVANUS Regional General Hospital, Central Kalimantan, from March 6–10, 2026, involving a 1-month-old female patient. Nutritional assessment included anthropometric, biochemical, clinical, and dietary intake parameters. The intervention consisted of a high-energy, high-protein liquid diet administered gradually via an Oral Gastric Tube. Results showed an increase in energy, protein, fat, carbohydrate, vitamin, and mineral intake. Clinical improvements were also observed, including relief from shortness of breath, strong crying, and active movement. Personalized nutritional strategies and education on breastfeeding and the importance of breast milk are crucial in caring for pediatric patients with complex medical and nutritional needs. The conclusion of this case study is that the gradual implementation of nutritional therapy in critically ill patients with severe communicating hydrocephalus can aid the recovery process and reduce the risk of complications.